2013
DOI: 10.1108/1536-541311318080
|View full text |Cite
|
Sign up to set email alerts
|

Influence of family control in the practice of earnings management

Abstract: Purpose -The purpose of this paper is to identify if the open Brazilian companies that have family control manage their accounting results in a negative way, and if this influence is in a positive sense of pushing the results down, that is, worsening their present profits due to future results. Design/methodology/approach -The empirical investigation is developed using as a sample 123 Brazilian companies listed on BM&FBovespa, totaling 1.353 observations for a period of 11 years (2000)(2001)(2002)(2003)(2004)(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…According to the literature, discretionary accruals are higher in family companies than in non-family firms (Wang, 2006), as the familycontrolled companies are more likely to have higher profits than non-family companies (Ali et al, 2007;Jaggi et al, 2009;Almeida-Santos et al, 2013). However, the literature shows that most of these studies were conducted in developed countries, and no single study has been conducted in the Middle East region.…”
Section: Family and Non-family Samplementioning
confidence: 99%
“…According to the literature, discretionary accruals are higher in family companies than in non-family firms (Wang, 2006), as the familycontrolled companies are more likely to have higher profits than non-family companies (Ali et al, 2007;Jaggi et al, 2009;Almeida-Santos et al, 2013). However, the literature shows that most of these studies were conducted in developed countries, and no single study has been conducted in the Middle East region.…”
Section: Family and Non-family Samplementioning
confidence: 99%
“…Evidence on the effects of family ownership on earnings management is mixed. For example, Rezaur Razzaque et al (2016) in Bangladesh, Chi et al (2015) in Taiwan, Almeida-Santos et al (2013) in Brazil, in addition to Alqatamin et al (2017) and Al- Haddad and Whittington (2019) in Jordan all reported a positive relation between family ownership and earnings management. On the other hand, Paiva et al (2019) found that earnings management in the UK is higher in family firms unless these are followed by financial analysts, whereas Prencipe et al (2008) found that earnings management for income smoothing purposes is lower in Italian family firms, and Chen et al (2015) found a similar relation in Japan.…”
Section: Related Party Transactions and Earnings Managementmentioning
confidence: 99%
“…As many authors have suggested (Angel & Carrasco Hernándezet, 2013;Bañegil Palacios et al, 2013), assigning family members to key decisionmaking positions can facilitate the achievement of family goals. Although some studies have argued that implicit trust among family members is a distinctive resource in family business that can generate social capital (Arregle et al, 2007), others have argued that both family altruism and family management may cause control problems and trigger agency problems such as moral hazard, and adverse selection ultimately leading to bad decision-making (Morck, 1996;Schulze et al, 2001Schulze et al, , 2002Almeida-Santos, et al, 2013). The ambiguous influence of family management raises important questions concerning its role in the growth strategies of FBGs.…”
Section: Fbgs' Internationalization Decisions: the Role Of The Internmentioning
confidence: 99%